Study of factors affecting contraceptive use among married women of reproductive Age - Bhandari, N; Shrestha, GK; Thakuri, PC (Journal of College of Medical Sciences-Nepal, 2014)
Background The use of contraception can prevent pregnancies related complication and helps in improving the women’s health and quality of their lives. Objective To explore reproductive characteristics among married women of reproductive age. To find out method of contraceptive use and side effects among married women of reproductive age. To uncover factors related to contraceptive use among married women of reproductive age. Methods This cross-sectional was carried out among (369) married couples of reproductive age group in ward number 5, 6 and 7 of Dhulikhel Municipality using purposive sampling. Those who fell in between the age group of (14-49 years) and willing to participate were included and pregnant women were excluded from the study. Questionnaire was used to obtain informations. Results Among 369(81.3%) of the respondents of reproductive age were using a modern contraceptive method. Regarding education 331(89.5%) of women’s and 352(95.1%) of husbands were literate and 275(91.6%) of women were found to be involved in decision making and had good inter-spousal communication that is 280(93.3%). Among the temporary method of family planning, Depo-Provera was the choice 150(54.5%) of contraceptive method. Conclusion The present study put more emphasis on increase in women’s literacy, women’s involvement in decision making and inter-spousal communication which helps to promote the effective use of contraceptive methods. As women play an important role in the decision making, women should be included in all aspects of reproductive health and family planning programs. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 24-29 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10233